Interaction between single vacancies in graphene sheet: An ab initio calculation. (August 2016) - Scopel, W.L.; Paz, Wendel S.; Freitas, Jair C.C.
Abstract: In order to investigate the interaction between single vacancies in a graphene sheet, we have used spin-polarized density functional theory (DFT). Two distinct configurations were considered, either with the two vacancies located in the same sublattice or in different sublattices, and the effect of changing the separation between the vacancies was also studied. Our results show that the ground state of the system is indeed magnetic, but the presence of the vacancies in the same sublattice or in different sublattices and the possible topological configurations can lead to different contributions from the π and σ orbitals to magnetism. On the other hand, our findings reveal that the net magnetic moment of the system with the two vacancies in the same sublattice move towards the value of the magnetic moment per isolated vacancy with the increase of the distance between the vacancies, which is ascribed to the different contributions due to π electrons. Moreover, it is also found that the local magnetic moments for vacancies in the same sublattice are in parallel configuration, while they have different orientations when the vacancies are created in different sublattices. So, our findings have clearly evidenced how difficult it would be to observe experimentally the emergence of magnetic order in graphene-based systems containing randomly created atomic vacancies, since the energy difference between cases of antiferromagnetic and ferromagnetic order decreases quickly with the increase in the distance separating each vacancy pair. Highlights: In order to investigate the interaction between single vacancies in a graphene sheet, we have used spin-polarized density functional theory (DFT). Two distinct configurations were considered, either with the two vacancies located in the same sublattice or in different sublattices, and the effect of changing the separation between the vacancies was also studied. Our results show that the ground state of the system is indeed magnetic, but the presence of the vacancies in the same sublattice or in different sublattices and the possible topological configurations can lead to different contributions from the π  and σ orbitals to magnetism. On the other hand, our findings reveal that the net magnetic moment of the system with the two vacancies in the same sublattice move towards the value of the magnetic moment per isolated vacancy with the increase of the distance between the vacancies, which is ascribed to the different contributions due to π electrons. Moreover, it is also found that the local magnetic moments for vacancies in the same sublattice are in parallel configuration, while they have different orientations when the vacancies are created in different sublattices. Thus, our findings have clearly evidenced how difficult it would be to observe experimentally the emergence of magnetic order in graphene-based systems containing randomly created atomic vacancies, since the energy difference between cases of antiferromagnetic and ferromagnetic order decreases quickly with the increase in the distance separating each vacancy pair.